(untitled) (Physical Education, Health and Social Sciences, 2025)
The purpose of this study is to identify the impact of debt financing and sales growth on organization performance of chemical companies listed on PSX. The study adopted quantitative approach. Data was collected through annual financial statement of the company present in annual reports of the company of chemical industry in Pakistan. The data collected was analyzed by using E-VIEWS software. The findings of the research show that there is an significant relationship between debt ratios and company performance ratios. The study contributes to theoretical and the practical knowledge as up till now no researches have been done by using this model on companies listed on PSX. Apart from this, the study conducted on the chemical sector of Pakistan provides originality in the literature of chemical sectors companies listed on PSX. The limitations of the study is that it is limited to chemical industries in Pakistan only and thus direct relationship has been checked using independent and dependent variables but it is recommended for the future researchers to conduct the study. Moreover, the future studies can be conducted on the other sectors listed on PSX belonging to other industries in different cities of Pakistan.